SAT0552 Fibroblast-Like Synovial Cells and Monocytes TEAM up in the Organization and the Dynamic Modeling of the Synovial Tissue. (10th June 2014) - Byrne, R.; von Dalwigk, K.; Steiner, G.; Holinka, J.; Windhager, R.; Smolen, J.S.; Kiener, H.; Scheinecker, C.
Abstract : Background: The synovial lining tissue consists of fibroblast-like synoviocytes (FLS) and monocyte-derived macrophage-like synoviocytes (MLS) within a self-built meshwork of dense extracellular matrix (ECM) components. FLS are thought to direct ECM synthesis, assembly and degradation. Whether this requires their cognitive interaction with MLS and whether FLS themselves or the ECM network serve as guiding structures for MLS migration is incompletely understood. Objectives: This tempted us to study the dynamics of synovial tissue modeling under steady state and inflammatory conditions using a 3D synovial tissue in vitro model. Methods: Human FLS were prepared from synovial tissues obtained as discarded specimens following joint arthroplasty. CD14 + monocytes (Mo) were isolated from peripheral blood. FLS and Mo were labeled with fluorescent membrane dyes and cultured in spherical extracellular matrix micromasses with an average size of 1.5 mm for up to two weeks. Second harmonic generation (SHG) was used for the visualization of collagen fibers. For stimulation experiments, micromasses were cultured in medium containing 10 ng/ml of tumor necrosis factor (TNF). Cell migration was monitored in individual micromasses by real-time confocal/multi-photon microscopy. Results: The formation of a FLS network was observed within 3-7 days and coincided with the detection of collagen fibers that co-localized with FLS. The majority of Mo was found to be in close contact with the FLS network with low tendency for migration. A minor fraction of Mo displayed a directed cell movement with an impressive maximum speed of up to 15 mcm/min. Rapid Mo migration occurred in intimate contact with FLS but did not necessarily follow FLS network boundaries. In addition, we observed the formation of Mo cell clusters that co-localized with collagen fibers in the absence of FLS. The addition of TNF i) increased the frequency and size of Mo cell clusters and ii) prolonged the overall mobility of Mo. Conclusions: The 3D synovial tissue culture system allows for monitoring and analyzing the dynamics of synovial lining modeling. Both, FLS and Mo appear to cooperate in the organization of the synovial lining tissue with subtle migration patterns of Mo in relation to the organized synovial lining architecture. Ongoing experiments address molecular mechanism(s) of Mo – FLS interaction in order to identify potential targets for future therapeutic intervention in arthritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3514